2018
DOI: 10.1074/jbc.ra118.003840
|View full text |Cite
|
Sign up to set email alerts
|

ROS-induced HSP70 promotes cytoplasmic translocation of high-mobility group box 1b and stimulates antiviral autophagy in grass carp kidney cells

Abstract: Autophagy plays many physiological and pathophysiological roles. However, the roles and the regulatory mechanisms of autophagy in response to viral infections are poorly defined in teleost fish, such as grass carp (Ctenopharyngodon idella), which is one of the most important aquaculture species in China. In this study, we found that both grass carp reovirus (GCRV) infection and hydrogen peroxide (H 2 O 2 ) treatment induced the accumulation of reactive oxygen species (ROS) in C. idella kidney cells and stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…Extracellular hepatic HMGB1 could also bind to the receptor for advanced glycation end products (RAGE) on uninfected cells (macrophages or HCs), which then triggers caspase-1 activation and pyroptosis as suggested by other studies. (29)(30)(31) Our data are consistent with other studies showing that genetic deletion of Hmgb1 or inhibition with HMGB1-neutralizing antibodies protects mice from lethal endotoxemia and sepsis. (30,31) Notably, our data show that cytosolic translocation of HMGB1 correlates with autophagy induction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Extracellular hepatic HMGB1 could also bind to the receptor for advanced glycation end products (RAGE) on uninfected cells (macrophages or HCs), which then triggers caspase-1 activation and pyroptosis as suggested by other studies. (29)(30)(31) Our data are consistent with other studies showing that genetic deletion of Hmgb1 or inhibition with HMGB1-neutralizing antibodies protects mice from lethal endotoxemia and sepsis. (30,31) Notably, our data show that cytosolic translocation of HMGB1 correlates with autophagy induction.…”
Section: Discussionsupporting
confidence: 91%
“…However, as suggested by others, translocation of HMGB1 to the cytosol following stressful stimuli may promote autophagy by direct interaction with beclin-1 (a key protein that initiates autophagosome formation), which results in separation of beclin-1 from Bcl2 apoptosis regulator (Bcl2). (29,30) This HMGB1-beclin1 complex is controlled at the transcriptional, posttranscriptional, and posttranslational level and is positively regulated by unc-51-like autophagy activating kinase 1 (Ulk1) and mitogen-activated protein kinase (MAPK). (29)(30)(31)(32) Our unpublished data suggest that MAPK plays a role in the induction of autophagy in HCs following IOE infection, as evidenced by phosphorylation and activation of the p38 MAPKs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CiTLR22a and CiTLR22b in lysosomes can efficiently sense dsRNA. Previous studies reported that GCRV enters cells by caveolae/raft-mediated endocytosis and induces autophagy (30,51). During autophagy, autophagosomes encapsulate GCRV and send them to lysosomes for degradation; thus, viral nucleic acids are fully exposed for binding CiTLR22a and CiTLR22b.…”
Section: Discussionmentioning
confidence: 99%
“…With the same method, CiTLR22a-myc, CiTLR22b-myc, MyD88-HA, TRIF-HA, and TIRAP-HA were ligated into pCMV-eGFP-CMV-SV40 to obtain overexpression vectors. Other localization fusion vectors (LAMP2-RFP, RAB5-RFP, RAB7-RFP, MyD88-RFP, TRIF-RFP, and TIRAP-RFP) and luciferase reporter plasmids (pIRF3pro-Luc, pIRF7pro-Luc, pIFN1pro-Luc, pIFN3pro-Luc, pIFNγ2pro-Luc, pNF-κB1pro-Luc, and pNF-κB2pro-Luc) were constructed in our previous studies (9,29,30). All the vectors were transfected into CIK cells by FuGENE R 6 Transfection Reagent (Promega) according to the manufacturer's instructions.…”
Section: Cell Culture Viral Infection and Reagentsmentioning
confidence: 99%
“…Overexpression plasmids RIG-I-HA and RIG-I-Flag were saved in our lab [21]. pDsRed1-C1-RAB5, pDsRed1-C1-RAB7, and pDsRed1-C1-LAMP2 for subcellular localization studies were also conserved in our lab [29,30]. For dual-luciferase reporter assays, the valid promoters (RIG-I, IPS-1, STING, TBK1, IRF3, IRF7, IFN1, IFN3, IFNγ2, and NF-kB1, respectively) were cloned into pGL3-basic luciferase reporter vector (Promega), which had been previously constructed in our lab [21,27].…”
Section: Plasmid Constructionmentioning
confidence: 99%